A comparison of acceptance and hopelessness levels of disabled preschool children's mothers - (:unkn) unknown (ELSEVIER SCIENCE BV, 2010)
The general purpose of this study was to compare the effects of certain variables on the acceptance issue of mothers with disabled children and their hopelessness levels. Mothers of 49 preschool children with autism and 52 with Down Syndrome, a total of 101 mothers, constituted the sampling of this study. Data were collected by the PARQ-Mother Version, Beck Hopelessness Scale and Personal Information Scale. The results revealed a linear relationship between acceptance and hopelessness levels in mothers of children with disability. It was found that mothers were more hopeless in case of rejection, whereas the hopelessness level decreased in case of acceptance. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Preschool period; disabled child; mother acceptance-rejection; hopelessness